Biosynthesis of Astaxanthin as a Main Carotenoid in the Heterobasidiomycetous Yeast Xanthophyllomyces dendrorhous - Barredo, Jose; García-Estrada, Carlos; Kosalkova, Katarina; Barreiro, Carlos (Journal of fungi (Basel), 2017)
Carotenoids are organic lipophilic yellow to orange and reddish pigments of terpenoid nature that are usually composed of eight isoprene units. This group of secondary metabolites includes carotenes and xanthophylls, which can be naturally obtained from photosynthetic organisms, some fungi, and bacteria. One of the microorganisms able to synthesise carotenoids is the heterobasidiomycetous yeast Xanthophyllomyces dendrorhous, which represents the teleomorphic state of Phaffia rhodozyma, and is mainly used for the production of the xanthophyll astaxanthin. Upgraded knowledge on the biosynthetic pathway of the main carotenoids synthesised by X. dendrorhous, the biotechnology-based improvement of astaxanthin production, as well as the current omics approaches available in this yeast are reviewed in depth.